Tax-benefit systems and the gender gap in income - Karina Doorley; Claire Keane (The Journal of Economic Inequality, 2023)
Abstract The gender wage gap and the gender work gap are sizable, persistent and well documented for many countries. The result of the gender wage and gender work gap combined is an income gap between men and women. A small literature has begun to examine how the tax-benefit system contributes to closing gender income gaps by redistributing between men and women. In this paper, we study the effect of tax-benefit policy on gender differences in income in the EU27 countries and the UK. We use microsimulation models linked to survey data to estimate gender gaps in market income (before taxes and transfers) and disposable income (after taxes and transfers) for each country. We then decompose the difference between the gender gap in market income and the gender gap in disposable income into the relative contribution of taxes and benefits in each country. We also isolate the relative contributions of the gender wage gap and the gender work gap to the overall gap in income between men and women in two of these countries.
Additional information: J16;J31
Keywords: 330; Gender inequality; Decomposition; Tax-benefit system